The Influence of Information Technology-Based Banking Services Against Customer Satisfaction - Elli Sulistyaningsih (Indonesian Journal of Banking and Financial Technology, 2023)
Increasingly advanced technology in the world of banking transactions began to use computer-based technology to facilitate transactions with customers. who used to serve customers by having to meet / customers come to bank branches provided by the bank where he used to save / invest it has become easier because banks have started using computer-based technology and now they can access via the internet even with mobile "cell phones" with SMS already used by many banks. The use of information and communication technology in national banking is relatively more advanced than other sectors. Various types of technology include Automated Teller Machines, Banking Application Systems, Real Time Gross Settlement Systems, Electronic Clearing Systems, and internet banking. Bank Indonesia itself often uses the term Banking Information System Technology (TSI) for all applications of information and communication technology in banking services. Another term that is more popular is Electronic Banking. Electronic banking covers a broad area of rapidly developing technology these days. Some of them are related to banking services at the "front line" or front end, such as ATMs and banking computerization (systems), and several other groups are back end, namely technologies used by financial institutions, merchants, or transaction service providers.